Association Between Types of Posterior Staphyloma and Refractive Error After Cataract Surgery for High Myopia - Wu, Jing; Wang, Ruochen; Liu, Can; Zhou, Yu; Jiang, Ziyuan; Liu, Fang (Frontiers in Neurology, 2021)
Purpose: To investigate the association between different types of posterior staphyloma (PS) and refractive error (RE) after cataract surgery in patients with high myopia. Methods: This retrospective study included 113 eyes of 113 highly myopic patients with PS. PS was detected using a wide-field fundus imaging system. PS was classified into wide macular, narrow macular, and other types. RE equaled the actual spherical equivalent (SE) minus the targeted SE values 3 months after cataract surgery. Results: The rates of wide macular, narrow macular, and other types of PS were 46.02, 39.82, and 14.16%, respectively. There were no significant differences in best corrected distance visual acuity (BCDVA) or SE among the three classifications of PS before cataract surgery (P > 0.05). However, postoperative BCDVA and SE were significantly different among the three types of PS patients (P < 0.05). The average RE values were 0.98 ± 1.00 D, 0.19 ± 0.87 D, 0.13 ± 0.59 D, respectively; the statistical differences of RE were <0.01, <0.01, and 0.81 (wide macular vs. narrow macular, wide macular vs. other types, narrow macular vs. other types), respectively. Multivariate linear regression analysis revealed that higher hyperopia RE after surgery was associated with wide macular staphyloma (P < 0.001), more myopic SE (P = 0.003), and increased BCDVA (P = 0.002) before surgery. Conclusions: Wide macular PS may be associated with more hyperopic RE; it may serve as a critical biomarker of hyperopic RE after cataract surgery in highly myopic patients.